Inter-firm collaboration and electronic business: Effects on profitability in Finland - Pekka Tsupari; Petri Rouvinen (The Research Institute of the Finnish Economy (ETLA), 2004)
This paper studies the joint effects of inter-firm collaboration and electronic business on firm profitability primarily in Finnish manufacturing. It is found that deeper forms of inter-firm collaboration boost financial performance but that high e-business intensity might even strain profitability. Firms that simultaneously have high inter-firm collaboration and e-business intensities as well as use electronic networks for conducting their collaboration are also more profitable. Based on this, two conclusions are drawn. First, suitable e-business practices facilitate inter-firm collaboration. Once in place, inter-firm collaboration tends to be immensely more productive with supporting electronic means. Second, e-business investment has to be accompanied with complementing organizational innovations, in this case a new form of external (and also internal, although not observed directly in the data used) organization of the firm, i.e., inter-firm collaboration. – – Tässä paperissa tutkitaan samanaikaisesti yritysten välisen yhteistyön tai verkostoitumisen ja sähköisen liiketoiminnan kannattavuusvaikutuksia lähinnä suomalaisissa teollisuusyrityksissä. Syvemmät yhteistyömuodot näyttävät parantavan niitä harjoittavien yritysten kannattavuutta. Sähköinen liiketoiminta puolestaan näyttäisi jopa laskevan kannattavuutta kuitenkin niin, että yritykset jotka harjoittavat samanaikaisesti laajamittaista yritysten välistä yhteistyötä ja sähköistä liiketoimintaa sekä käyttävät elektronisia tietoverkkoja keskinäisen yhteistyönsä välineenä ovat kannattavampia. Tähän löydökseen perustuen tutkimuksessa tehdään kaksi johtopäätöstä. Ensiksi, tietyt sähköisen liiketoiminnan muodot tukevat yritysten välistä yhteistyötä. Kun nämä elektroniset välineet on otettu käyttöön, ne tehostavat merkittävästi keskinäistä kanssakäymistä. Toiseksi, kannattaviin sähköisen liiketoiminnan investointeihin liittyvät täydentävät organisatoriset innovaatiot, tässä tutkimuksessa siis uudet ulkoiset (ja epäilemättä myös sisäiset, joskaan niitä ei käytetyssä aineistossa havaita suoraan) kanssakäymisen muodot.
Keywords: 330; Electronic business; Profitability; Inter-firm relations; Partnerships; Cooperation; Collaboration; Networking; Sähköinen iiketoiminta; kannattavuus; yritysten väliset suhteet; kumppanuus; yhteistyö; yhteistoiminta; verkottuminen; verkostoituminen; E-Business; Unternehmenskooperation; Rentabilität; Finnland